Monetary policy, indeterminacy and learning - George W. Evans; Bruce McGough (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
The development of tractable forward looking models of monetary policy has lead to an explosion of research on the implications of adopting Taylor-type interest rate rules. Indeterminacies have been found to arise for some specifications of the interest rate rule, raising the possibility of inefficient fluctuations due to the dependence of expectations on extraneous 'sunspots'. Separately, recent work by a number of authors has shown that sunspot equilibria previously thought to be unstable under private agent learning can in some cases be stable when the observed sunspot has a suitable time series structure. In this paper we generalize the 'common factor 'technique, used in this analysis, to examine standard monetary models that combine forward looking expectations and predetermined variables. We consider a variety of specifications that incorporate both lagged and expected inflation in the Phillips Curve, and both expected inflation and inertial elements in the policy rule. We find that some policy rules can indeed lead to learnable sunspot solutions and we investigate the conditions under which this phenomenon arises.
urn:nbn:de:hebis:30-10424
Keywords: E52; E32; D83; D84; 330; Monetary Policy; sunspots; expectations; learning; stability; Geldpolitik; Erwartungstheorie; Lernprozess; Theorie